Impact of Flexible Work Arrangements on Employee Job Satisfaction in Zambia - Mulikita, Susan (European Journal of Human Resource, 2024)
Purpose: The aim of the study was to assess the impact of flexible work arrangements on employee job satisfaction in Zambia. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that when employees are allowed flexibility in their work schedules, such as the ability to work from home, choose their own hours, or have compressed workweeks, they tend to report higher levels of job satisfaction. This increase in satisfaction is largely attributed to improved work-life balance, reduced commuting stress, and the autonomy to manage their time effectively. Furthermore, flexible work arrangements can lead to increased productivity and lower turnover rates, as employees feel more trusted and valued by their employers. These arrangements also cater to diverse needs, accommodating those with family responsibilities, health issues, or other personal commitments, thereby enhancing their overall well-being and job satisfaction. However, the success of such arrangements depends on effective communication, clear expectations, and support from management to ensure that both organizational goals and employee needs are met. Implications to Theory, Practice and Policy: Job characteristics theory, self-determination theory and conservation of resources theory may be used to anchor future studies on assessing the impact of flexible work arrangements on employee job satisfaction in Zambia. Organizations should implement flexible work policies that offer a range of FWAs, including telecommuting, flexible hours, compressed workweeks, and job sharing, to cater to diverse employee needs and preferences. Policymakers should advocate for flexible work legislation that supports the implementation of FWAs across industries and sectors, ensuring that employees have legal protections and rights when engaging in flexible work arrangements.